Colonization and strategic stratification of butterfly Pachliopta aristolochiae (Lepidoptera: Papilionidae) and its relationship with the host plant Aristolochia indica (Piperales: Aristolochiaceae) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Colonization experiment for the butterfly Pachliopta aristolochiae (Fabricius, 1775) (Lepidoptera: Papilionidae) was carried out in the Zoological Garden, Curzon Hall, University of Dhaka and Bhawal national park, Gazipur from 2010 to 2011, and butterfly host-plants and nectar-plants were identified for this purpose. The field observations and identification confirmed that the host plant species Aristolochia indica is a creeper plant. A. indica was cultivated for the butterfly oviposition behaviour and to continue developmental stages. The oviposition behaviour of gravid female, hatching, feeding and moulting behaviour of the four larval instars, and pupation behaviour of A. indica were recorded. Both laboratory and field observations revealed that while there was availability of food, 1st and 2nd instar larvae preferred tender leaves, whereas the 3rd and 4th instar larvae fed both on young and mature leaves. However, mature larvae were also observed to feed on the stems, flower and fruits of the host-plant in absence of suitable succulent leaves. The feeding time was recorded for each larval instars and it was relatively low for 1st and 2nd instar larvae, remarkably higher in 3rd instar larvae and highest in the case of ultimate and penultimate larval instars. The egg, larval and pupal mortalities were counted during the study period. Their survivability rate was 80% or more. This result was found to stand good for a successful colonization process of the butterfly P. aristolochiae.J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 45-54